2020
DOI: 10.21203/rs.3.rs-20941/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification the prognostic value of immune gene signature and infiltrating immune cells of esophageal cancer patients

Abstract: Background Esophageal cancer (ESCA) is one of the deadliest solid malignancies with worse survival in the world. The poor prognosis of ESCA is not only related to malignant cells, but also affected by the microenvironment. We aimed to establish prognostic signature consisting of immune genes to predict the survival outcome of patients and estimate the prognosis value of infiltrating immune cells in tumor microenvironment (TME). Methods Based on integrated analysis of gene expression profiling and immune gene d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(40 reference statements)
0
4
1
Order By: Relevance
“…In this study, the complex value was positively correlated with macrophage M0, and myeloid dendritic cell activated while negatively correlated with T cell CD4+ memory resting, T cell regulatory (Tregs), and mast cell activated. A recent study reported a prognostic model established by immune genes associated with memory CD4+ T cells, follicular helper cells, and monocytes for patients with ESCA [50], which was inconsistent with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the complex value was positively correlated with macrophage M0, and myeloid dendritic cell activated while negatively correlated with T cell CD4+ memory resting, T cell regulatory (Tregs), and mast cell activated. A recent study reported a prognostic model established by immune genes associated with memory CD4+ T cells, follicular helper cells, and monocytes for patients with ESCA [50], which was inconsistent with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with our results was the prognostic value found in a prognostic model established by immune genes associated with memory CD4 + T cells, Tfh cells for patients with EC. 55 Furthermore, plasma cells, endothelial cells, Tfh cells, and Tregs were upregulated, while CAFs and NK cells were downregulated in the high-risk group compared with the low-risk group in our model. M2 Macrophages induced enhanced the process of epithelial-mesenchymal transition and immune escape through the PD-1 signaling pathway, promoting the ESCC exacerbation which let ESCC patients have a poor prognosis.…”
Section: Discussionmentioning
confidence: 61%
“…With the advancement of bioinformatics, e cient algorithms have accelerated the transition of various omics big data to new therapeutic targets. As one of the most robust algorithms for analyzing immune cell in ltration-CIBERSORT-has been used in multiple tissues [13][14][15]. In this study, we used it to explore the landscape of immune in ltration in the glomerulus of DN.…”
Section: Discussionmentioning
confidence: 99%